2020
DOI: 10.13188/2327-204x.s200005
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Adamantanes with Transmitter Receptor Antagonist Properties for the Prevention/Treatment of COVID-19

Abstract: Members of the adamantane family of agents in general and two such members, amantadine and memantine, in particular, have established beneficial actions across a wide range of infectious diseases including those caused by coronaviruses. Increasing evidence suggests that the protective effects of these agents is the result of actions on neurotransmitter systems namely the NMDA receptor subclass of the glutamatergic system and by the α7-nACh subclass of nicotinic cholinergic receptor. The potent NMDA receptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…Future studies should investigate the mechanism of action and SARS-CoV-2 targets of the tested inhibitors. In vitro studies suggested amantadine to target SARS-CoV-2 protein E, which was suggested to have ion-channel function [ 6 , 25 ]. Further, amantadine was shown to inhibit the expression of a lysosomal gene involved in the viral entry of SARS-CoV-2 in vitro [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate the mechanism of action and SARS-CoV-2 targets of the tested inhibitors. In vitro studies suggested amantadine to target SARS-CoV-2 protein E, which was suggested to have ion-channel function [ 6 , 25 ]. Further, amantadine was shown to inhibit the expression of a lysosomal gene involved in the viral entry of SARS-CoV-2 in vitro [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Binding of the SARS-CoV-2 spike to ACE2 is followed by action of the endosomal cysteine protease Cathepsin L [CTSL], resulting in fusion of viral and host cell membranes and release of the viral genome into the host cell cytoplasm. Amantadine has the potential to disrupt the process by down-regulation of CTSL by increasing the pH of endosomes, resulting in impaired viral entry and replication [ 20 ] …”
Section: Adamantanes Against Sars-cov-2: In Vitro and Preclinical Investigationsmentioning
confidence: 99%
“…Damage to the central nervous system (CNS) is well established in COVID-19 and it has been suggested that the neuroinvasive nature of SARS-CoV-2 may contribute to the acute respiratory failure characteristic of COVID-19 [ 19 ]. There is evidence to suggest that amantadine and memantine exert their protective effects against COVID-19 via mechanisms involving specific CNS neurotransmitter systems [ 20 ]. Both amantadine and memantine are potent antagonists of the NMDA subclass of glutamate receptor and memantine prevents motor incoordination problems in animals infected with the neuroinvasive HCoV-OC43 with concomitant suppression of viral replication in a dose-dependent manner.…”
Section: Adamantanes Against Sars-cov-2: In Vitro and Preclinical Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Вовлечение стволовых структур может способствовать развитию острой дыхательной недостаточности, характерной для COVID-19 [20][21][22]. Амантадин и мемантин не только реализуют свой защитный потенциал в отношении центральной нервной системы, блокируя нейроинвазию, но и обладают нейропротекторным эффектом, влияя на механизмы эксайтотоксичности, оксидативного стресса, нейровоспаления за счет блокады NMDA-рецепторов [23][24][25] (рис. 2).…”
Section: Introductionunclassified